2018
DOI: 10.1007/s00415-018-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for self-harm in people with epilepsy

Abstract: ObjectiveTo estimate the risk of self-harm in people with epilepsy and identify factors which influence this risk.MethodsWe identified people with incident epilepsy in the Clinical Practice Research Datalink, linked to hospitalization and mortality data, in England (01/01/1998–03/31/2014). In Phase 1, we estimated risk of self-harm among people with epilepsy, versus those without, in a matched cohort study using a stratified Cox proportional hazards model. In Phase 2, we delineated a nested case–control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…Separately in each dataset, we identified people as having incident epilepsy if they had the first evidence of a code for epilepsy diagnosis and an associated prescription for an antiepileptic drug (AED) in the month before or 6 months after the diagnosis. The requirement for both an epilepsy diagnosis and AED treatment is suggested to increase the reliability of the ascertainment of epilepsy in observational studies, by the International League Against Epilepsy (ILAE) ( 12 ) and is a definition we have previously applied in epidemiological studies of epilepsy ( 13 ). The use of primary care records in the SAIL Databank to identify people with epilepsy has been validated ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Separately in each dataset, we identified people as having incident epilepsy if they had the first evidence of a code for epilepsy diagnosis and an associated prescription for an antiepileptic drug (AED) in the month before or 6 months after the diagnosis. The requirement for both an epilepsy diagnosis and AED treatment is suggested to increase the reliability of the ascertainment of epilepsy in observational studies, by the International League Against Epilepsy (ILAE) ( 12 ) and is a definition we have previously applied in epidemiological studies of epilepsy ( 13 ). The use of primary care records in the SAIL Databank to identify people with epilepsy has been validated ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies indicate that people who are taking 2 or more AED are at increased risk of suicidality and non-fatal self-harm behaviors. A study done in England showed an increased risk of suicidality for two AED with (OR 1.84, 95% CI 1.33-2.55) or three or more AEDs (OR 2.44, 95% CI 1.51-3.94) (10,23). similarly, trials on 11 types of AEDs from a pharmaceutical company on 28 000 patients showed a risk increase by almost 2 times (OR 1.8 95% CI, 1.24-2.66) (6, 32).…”
Section: Characteristicsmentioning
confidence: 99%
“…A cut-off value of PHQ-9 ≥ 5 was used to identify depression. severity scores consist of none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). The third section was a tool to identify and assess Suicidality.…”
Section: Data Collection and Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…Percebeu-se um risco cinco vezes maior associado ao histórico de uso indevido de álcool e outras substâncias. Isso poderia contribuir para o aumento do risco de automutilação experimentado por esses indivíduos (Gorton et al, 2018).…”
Section: Diagnóstico Prévio De Transtorno Mentalunclassified